Whole-body computed tomography in severely injured patients. Issue 1 (February 2018) - Huber-Wagner, Stefan; Kanz, Karl-Georg; Hanschen, Marc; van Griensven, Martijn; Biberthaler, Peter; Lefering, Rolf
Abstract : Purpose of review: To provide an update on the relevant and recent studies on whole-body computed tomography (WBCT) imaging of severely injured patients. Recent findings: The advantages of WBCT in time saving, diagnostic accuracy and even in survival have been proven in numerous studies. WBCT can also be beneficial in haemodynamically unstable major trauma patients. The CT scanner should be located close to the emergency department or even in the trauma room. The issue of radiation is still quite important, however, iterative as well as split-bolus protocols can nowadays reduce radiation significantly. The question: which trauma patient should receive WBCT and which not is not yet solved sufficiently. Postmortem WBCT has a promising potential to promptly define the definitive cause of death of trauma victims comparably to traditional autopsy. Summary: On account of the recent advances, whole-body CT has become a crucial part of the initial in-hospital assessment of severely injured patients. It is recommended as the standard radiological tool for the emergency diagnostic work-up in major trauma patients.